Pemanfaatan Zoom Meeting untuk Proses Pembelajaran pada Masa Pandemi Covid-19 - Danin Haqien; Aqiilah Afiifadiyah Rahman (SAP (Susunan Artikel Pendidikan), 2020)
During the COVID-19 pandemic, each university in Jakarta and Depok performs a distance learning system. A widely used application during distance learning is a Zoom Meeting. This research was conducted to know the effectiveness of Zoom Meeting application to students in Jakarta and Depok during COVID-19 Pandemic. This research was a qualitative with grounded theory method.  Data collection techniques were conducted with interviews through Google Form and Whatsapp to thirty two university students in Jakarta and Depok. The results of this study, showed that the use of Zoom Meeting application was not very effective for university students in Jakarta and Depok. However, the Zoom Meeting app was better because, in the application of Zoom Meeting communication between individuals was done orally compared to the use of a learning application that conductedwritten communication activities according to education communication theory.